Gene Expression of FSHR Gene in Infertile Women Undergone IVF Program - Akram, Sarah M.; Akram, Sally M.; Samawi, Farah Thamer; Attallah, Ahmed Mahmood (American Journal of Biology and Natural Sciences, 2025)
One of the main obstetric diseases that may cause pelvic discomfort and infertility is endometriosis (1). The link between endometriosis and fertility has long been underlined and the problem is one does not quite understand the part that endometriosis-related infertility play (2). The pregnancy and implantation rates in women who underwent endometriosis and were exposed to IVF treatment, was compared with those that were not afflicted by the problem of endometriosis (3).